Analysis of errors in investors` applications in the procedure of obtaining a building permit - Leśniak, Agnieszka; Górka, Monika; Kargol, Anna (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
One of the most important documents occurring in the investment process is the administrative decision: building permit. Obtaining it is often a time-consuming process in practice, associated with the need to attach to the application other required decisions and permits necessary for a positive consideration of the case.
Keywords: building permit; Construction law; administrative decision; pozwolenie na budowę; prawo budowlane; decyzja administracyjna